Effects of different mycorrhizas on the quality of northern highbush blueberries - Lundström, Anna (SLU/Dept. of Plant Breeding (from 130101), 2017)
Blueberries contain components like for instance triterpenes and stilbenes which have potentially protective roles against many human diseases. These substances are also important at threats from herbivores and fungi attacks to plants. Quality traits assessed in this study was the amount of healthy substances like triterpenes, stilbenes, but also sugar/acid ratio which are important for flavor.